The economic evaluation of compost producing and other sorted materials in Wadi Al-Hadda plant in Tartous governorate - محسن جحجاح,; حيان سليمان,; رائد جعفر ,; احمد حموده, (Latakia University Journal -Biological Sciences Series, 2022)
The research aims to study the costs of compost manufacturing, and other excretions within the plant (plastic materials, aluminum, nylon bags, paper, cardboard, glass) and their economic returns. The research was conducted in the Wadi Al-Hadda plant for solid waste treatment, in Tartous Governorate. Through the research, average production costs and returns, some income indicators and economic efficiency indicators were calculated, and the study period was during the first quarter of 2020, where the exchange rate was almost stable at about 1000 SP / dollar. The value of the total production costs amounted to (521,342,640 million SP / year), the total net product amounted to (598,077,360 million SP / year), and the net income was (453,204,000 million SP / year), while the net economic return amounted to (410,157,360 million SP/year), and the profitability coefficient compared to the basic production costs amounted to 106.94%, the profitability coefficient compared to the invested capital was 78.67%, while the payback period for the invested capital was 1.27 years